Anxiety and depression mediate the relationship between insomnia symptoms and the personality traits of conscientiousness and emotional stability. Issue 6 (June 2019) - Akram, Umair; Gardani, Maria; Akram, Asha; Allen, Sarah
Abstract: This study examined the relationship between the Big Five personality traits and insomnia symptoms in the general population. Additionally, the mediating role of anxiety and depression was examined. Participants (N = 625) completed online measures of the big five personality traits and insomnia severity. Insomnia symptoms were independently related to extroversion, agreeableness, conscientiousness, emotional stability, anxiety and depression in univariate analysis. Linear regression determined conscientiousness and emotional stability to be the only traits predicting insomnia symptoms. However, these relationships were at least partially mediated by anxiety and depression. Whilst reduced levels of conscientiousness and emotional stability has previously associated with poor sleep and insomnia, the current outcomes shed light on the mechanisms which serve to mediate this relationship.